Ubiquitination Events That Regulate Recombination of Immunoglobulin Loci Gene Segments - Chao, Jaime; Rothschild, Gerson; Basu, Uttiya (Frontiers in Immunology, 2014)
Programmed DNA mutagenesis events in the immunoglobulin (Ig) loci of developing B cells utilize the common and conserved mechanism of protein ubiquitination for subsequent proteasomal degradation to generate the required antigen-receptor diversity. Recombinase proteins RAG1 and RAG2, necessary for V(D)J recombination, and Activation-Induced cytidine Deaminase (AID), an essential mutator protein for catalyzing class switch recombination (CSR) and somatic hypermutation (SHM), are regulated by various ubiquitination events that affect protein stability and activity. Programmed DNA breaks in the Ig loci can be identified by various components of DNA repair pathways, also regulated by protein ubiquitination. Errors in the ubiquitination pathways for any of the DNA double strand break repair proteins can lead to inefficient recombination and repair events, resulting in a compromised adaptive immune system or development of cancer.